Pengembangan Sistem Manajemen Klinik Hewan Berbasis Web (Studi Kasus: Rakki Pet Clinic & Klinik Hewan UB) - Fadel Muhammad Hasanuddin; Achmad Arwan; Faizatul Amalia (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Rakki Pet Clinic and UB Pet Clinic are two of many clinics located in malang. Some of their services are clinic, grooming, pet shop, and pet hotel. In a month, their patient can reach 350 to 500 patients. With this range of patients, Rakki Pet Clinic and UB Pet Clinic are still documenting their business processes manually, starting from patient registration, medical records, to recap of personnel activities. The manual documentation process will complicate the service process and will cause problems, for example in the search for scattered medical records, errors in writing medical records, patient registration, doctor appointments, and recap of personnel activities that do not match digitally recorded data. This can be detrimental to the time, effort, health and finances of all parts involved, from the animal itself, the owner of the animal, the owner of the clinic, to the paramedics. System development that utilizes web-based technology is a solution to these problems. This study aims to determine the system requirements, system design, and implementation of a web-based veterinary clinical management system developed using the waterfall method. The results of the needs analysis in this study obtained 50 functional systems and 5 actors who will be directly related to the system. Systems are tested using unit testing, integration testing, validation testing, and compatibility. All test results obtained are 100% valid, indicating the system is able to run as expected